Organizational Factors and Change Strategies Associated With Medical Home Transformation. (July 2015) - Solberg, Leif I.; Stuck, Logan H.; Crain, A. Lauren; Tillema, Juliana O.; Flottemesch, Thom J.; Whitebird, Robin R.; Fontaine, Patricia L.
There is limited information about how to transform primary care practices into medical homes. The research team surveyed leaders of the first 132 primary care practices in Minnesota to achieve medical home certification. These surveys measured priority for transformation, the presence of medical home practice systems, and the presence of various organizational factors and change strategies. Survey response rates were 98% for the Change Process Capability Questionnaire survey and 92% for the Physician Practice Connections survey. They showed that 80% to 100% of these certified clinics had 15 of the 18 organizational factors important for improving care processes and that 60% to 90% had successfully used 16 improvement strategies. Higher priority for this change ( P = .001) and use of more strategies ( P = .05) were predictive of greater change in systems. Clinics contemplating medical home transformation should consider the factors and strategies identified here and should be sure that such a change is indeed a high priority for them.